Perlindungan Pengguna Jasa Penitipan Hewan Peliharaan Terhadap Kelalaian Pelaku Usaha Menurut Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Gabriele Amelia Christie; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2022)
Consumers get the protection which is regulated in Law Number 8 of 1999 concerning Consumer Protection. Article 7 letter A contains that business actors are obliged to have good faith will in carrying out their business activities related to the objective of establishing consumer protection, namely creating a quality business world. In fact, the goal of consumer protection has not been achieved optimally, because it can be seen that the high number of cases related to consumer protection as resulted in an imbalance between business actors and consumers. An imbalance occurred in the case of a dog named Maxi of the English Bulldog race who was injured and had to be operated on due to negligence caused by the business actor as animal care for consumers as users of animal care services. This case relates to consumer protection which caused the consumer to suffer losses and agreement that was violated by business actors causing negligence. The application of consumer protection that is not in line with Law Number 8 of 1999 concerning Consumer Protection creates problems. This research is normative legal research. The results of the research show that there are consumer rights that have been harmed and have not yet been fulfilled based on Law Number 8 of 1999 concerning Consumer Protection and that regulations are needed to support the protection of animal care.